From Text(s) to Screen: Adapting Genius. - ZAHLAN, ANNE R. (Thomas Wolfe Review, 2017)
The article focuses on the making of Michael Grandage's film "Genius" adapted from the book "Maxwell Perkins: Editor of Genius," by A. Scott Berg. It discusses the challenges involved in film adaptation and also highlights the relationship between Grandage and screen play writer John Logan. The author also analyzes the cast and characters in the film.